PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, ALOKASI KHUSUSTERHADAP BELANJA MODAL - Mufida, Binti Amaliyah; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to prove the influence of Local Own-Sources Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) to the Capital Expenditure (BM) at the districts / cities at East Java. The population is 38 districts / cities in East Java. The data collection method uses the secondary data; the data has been obtained by using documentation and the Central Bureau of Statistics (BPS) which has been published. The observation periods of this research is during 5 year periods in 2010-2014 and the amounts of the research data (n) are 190 samples.The result of this research shows that PAD has positive influence to the capital expenditure. It is in accordance with the hypothesis test which has been done by using multiple linear regressions that shows the p value is 0.000 which is smaller than ï¡ 0.05 and the value of b is 0.489. For DAU shows that it does not have any influence to the capital expenditure which is p value 0.448 is greater than ï¡ 0.05 with the value of b is 0,028. Meanwhile, the DAK has positive influence, it shows p value is 0.000 which is smaller than ï¡ 0.05 with the value of b is 0.170.Keywords: Local Own-Sources Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Capital Expenditure (BM)